2021
DOI: 10.1038/s41392-021-00742-w
|View full text |Cite
|
Sign up to set email alerts
|

A dual-role of SARS-CoV-2 nucleocapsid protein in regulating innate immune response

Abstract: The recently emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is the causative agent of ongoing global pandemic of COVID-19, may trigger immunosuppression in the early stage and overactive immune response in the late stage of infection; However, the underlying mechanisms are not well understood. Here we demonstrated that the SARS-CoV-2 nucleocapsid (N) protein dually regulated innate immune responses, i.e., the low-dose N protein suppressed type I interferon (IFN-I) signaling and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 48 publications
2
77
0
Order By: Relevance
“…Recently, Zhao et al reported that the structural N protein may play a dual-role in regulating IFN signaling based on its expression level, i.e., the low-dose N protein was suppressive, while the high-dose was promotive, for the IFN response. This worked out by dually regulating the phosphorylation and nuclear translocation of IRF3, partially explaining how IFN signaling was activated [34]. As an alternative, our data provided an additional way for SARS-CoV-2 RNA virus to activate IFN response unexpectedly via cGAS-STING signaling pathway, which was secondary to the formation of multinucleate syncytia between cells expressing spike and ACE2.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, Zhao et al reported that the structural N protein may play a dual-role in regulating IFN signaling based on its expression level, i.e., the low-dose N protein was suppressive, while the high-dose was promotive, for the IFN response. This worked out by dually regulating the phosphorylation and nuclear translocation of IRF3, partially explaining how IFN signaling was activated [34]. As an alternative, our data provided an additional way for SARS-CoV-2 RNA virus to activate IFN response unexpectedly via cGAS-STING signaling pathway, which was secondary to the formation of multinucleate syncytia between cells expressing spike and ACE2.…”
Section: Discussionmentioning
confidence: 72%
“…Many viruses that have co-evolved with their hosts have developed complex and multiple strategies to subvert or antagonize the host innate immune response as a mechanism to evade immune detection and elimination. Indeed, it has become increasingly clear that multiple SARS-CoV-2 encoded genes products target innate immune signaling pathways at various levels ( Xia et al., 2020 ; Fung et al., 2021 ; Han et al., 2021 ; Kumar et al., 2021 ; Sui et al., 2021a ; Vazquez et al., 2021 ; Zhao et al., 2021 ). Here we identify the Spike protein of SARS-CoV-2 as a key negative regulator of IFN-I activation in the RIG-I pathway that targets the IRF3 transcription factor and mediates its proteasomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Lethal pneumonia pathogenesis is usually associated with respiratory failure, resulting from cytokine storm-induced airway obstruction or alveolar epithelial damage [ 65 69 ]. We found that upregulated glycolysis, OXPHOS, glutathione metabolism, and sphingolipid metabolism may promote AT1 cell aging.…”
Section: Resultsmentioning
confidence: 99%